The lived experiences of the spouses of alcohol dependent partners: a phenomenological study - Mini George; Naorem B Devi (Inishmore Laser Scientific Publishing Ltd, 2022)
# Background Alcoholism is rising in India, affecting both individuals and their families. This study explored the lived experience of women cohabiting men with alcohol use disorder (AUD) to understand the experience and coping resources they adopted from their perspective. # Methods Interpretive phenomenology design was used. Purposive sampling was employed to select women cohabiting men with AUD attending the de-addiction clinic. After explaining the study and written informed consent, in-depth interviews were conducted. By the interview of the 11^th^ participant, data saturation was reached. # Results Thematic analysis was undertaken. Significant statements and meaning units were identified, and codes were assigned. Three categories, namely impact on self, effect on life and coping strategies, were developed, and two main themes (*faced numerous challenges* and *used adaptive and maladaptive coping)* were generated. # Conclusions Women faced innumerable problems of poor health, physical misery, marital discord, emotional disturbances, strained social relations, and financial burden. Most women relied heavily on avoidance or tolerance coping like covering up, taking on extra work, withdrawing, distancing, and hiding from friends and family. Putting on a brave front and not doing anything is not productive for women and men with AUD.